UPAYA ORANG TUA DALAM MENINGKATKAN MINAT BACA ANAK USIA SEKOLAH DASAR - Sobari, Ari Abdi; Suherman, Maman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Reading interest is a fundamental foundation for developing children's literacy skills, yet many elementary school students still demonstrate low reading interest. This study aims to describe how parenting patterns influence children's reading interest at SDN Hegarmanah 02, Sukamanah Village. The method used is descriptive qualitative with a case study approach. Data were collected through interviews, observations, and documentation involving parents, teachers, and students. The results show that democratic parenting has a positive impact on children's reading interest through emotional support, role modeling, and shared reading routines. Conversely, authoritarian and permissive parenting patterns tend to hinder reading interest due to lack of dialogue, role modeling, and supervision. Additionally, inhibiting factors such as limited parental time, minimal reading facilities at home, low parental education levels, and children's dependency on gadgets also influence the low parental participation in supporting reading activities. The study found that mothers play a more dominant role in shaping children's reading habits through direct involvement and providing reading materials. School literacy programs show better results when supported by consistent parenting at home. These findings emphasize the importance of parenting patterns and parental involvement in shaping children's literacy culture from an early age. The research recommends strengthening collaboration between families and schools in creating a supportive reading environment.